Efektivitas Penerapan Konseling Gestalt Melalui Teknik Reframing Untuk Menurunkan Perilaku Internet Addiction Pada Siswa Di SMP (Suatu Penelitian di SMPN 1 Banda Aceh) - Fattayatinur Fattayatinur; Nurhasanah Nurhasanah; Abu Bakar (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2018)
Continuous use of the internet can get negative effects for every individual who uses it. In this case the reframing technique is one of the alternatives to break the behavior of addiction to the internet. This study aims to determine the effectiveness of the application of reframing techniques using the gestalt approach in reducing the behavior of Internet addiction. this study includes the type of pre-experimental research using a quantitative approach.The population of this study were 70 students in the class vii SMPN 1 Banda Aceh while the sample used included 30 students selected from the population. The sampling technique is purposive sampling. Data collection techniques used is a Likert scale questionnaire while data anaisis technique using paired T test (paired sample T-test). The results showed that the average value of pretest was 112.77 higher than the mean posttest score of 68.90. In addition, the value of t arithmetic results obtained that thitung ≥ ttabel is 17.269 ≥ 2.045 with a significant level of 5% or 0.05 which means the alternative hypothesis (Ha) and nil hypothesis (H0) rejected. In other words, the application of gestalt counseling through effective reframing techniques to be used in reducing Internet Addiction behavior. Keywords: Gestalt Counseling Approach, Reframing Technique, Internet addiction